Foundations of quantum chromodynamics : An introduction to perturbative methods in gauge theories - Muta, T (World scientific lecture notes in physics, 1998)
This book provides a systematic introduction to the foundations of quantum chromodynamics (QCD), focusing on perturbative techniques and their applications to gauge theories. It serves as a comprehensive reference for graduate students and researchers in theoretical physics.